The Weiss judgment: The Court's further clarification of the ECB's legal framework: Case C-493/17 Weiss and others, EU:C:2018:1000. Issue 3 (June 2019) - Mooij, Annelieke AM
In December 2018, the Grand Chamber of the European Court of Justice delivered its judgment in the Weiss case. This case is the most recent development in the Euro crisis case law. The financial crisis has shown the difficulty in determining the precise limits to the mandate of the European Central Bank. The Gauweiler case provided a legal framework but also left unanswered questions. This contribution will first provide the background to the Euro crisis and the context of the case then continue by giving a short summary and analyses of the Opinion of the Advocate General and the judgment of the Court. Finally, a reflection will be given on what lessons can be taken from the Weiss case. As the Weiss case appears to be last in Euro crisis case law, this reflection will include an overall analysis of the current interpretation of the mandate of the European Central Bank post-Euro crisis.